Study the predictive relationship of Chinese geese breeding growth in local conditions in Iraq - Zainab Zedan Al-Muzani , Majid Hassan Al-Asadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study was conducted in the field of waterbirds in the Animal Production Department / College of Agriculture / Basra University for the period from 11/30/2020 to 2/6/2021. 50 geese breed (25 males and 25 females), white and gray geese, were reared from 1 d. Feed and water were provided ad libitum. The birds and feed consumed were weighed weekly at age (14,28,42,56, 70) in the experiment. Gompertz was used to describe the growth curve and calculate the predictive growth rates for both body weight, weight gain, time at the transformation point and highest weekly weight gain. The results showed a significant effect for species and gender, as the white and male geese were significantly superior in body weight, the amount of weight gain, and the efficiency of food conversion on the gray and females, while there were no significant differences in the amount of feed consumed, and the average body weight at the transformation point reached (3749.56, 3519.59) g For White and Gray, respectively, with a lifespan of 112 days. While the weight gain and the feed consumed at the same point were (562.06, 543.61), (2680.10, 2689.11) gm for white and gray geese, respectively, at the age of 70 days. Gompertz applied with high accuracy in the amount of feed consumed, reaching 0.98, while it reached (0.31, 0.25), and (0.82, 0.79) for the white geese and the lead geese, respectively.